A portable instrument for monitoring acute water toxicity based on mediated electrochemical biosensor: Design, testing and evaluation. (September 2020) - Yang, Yajie; Liu, Yanran; Chen, Yafei; Wang, Yu; Shao, Peng; Liu, Runze; Gao, Guanyue; Zhi, Jinfang
Abstract: A water quality early-warning instrument for evaluating acute water toxicity based on the electrochemical biosensor, Model ETOX18-01, was developed and manufactured with the features of low current detection (0.1 nA), precise thermostatic control, self-cleaning as well as remote data transmission. A sensitive integrated microbial electrode, made up of a glass carbon electrode that was modified by an active biofilm consisting of Escherichia coli, thionine, carbon nanodots and chitosan, has been fabricated as the biosensor. To validate the performance, multiple real water samples and artificial water samples were tested by Model ETOX18-01, and compared with ISO standardized luminescent bacterial test simultaneously. The correlation between the Model ETOX18-01 and luminescent bacterial test for these water samples showed good determination coefficient (R 2 = 0.9827). In addition, Model ETOX18-01 is more sensitive to colored metal ionic samples. With its characteristics of high sensitivity, excellent repeatability and easy operation, the instrument Model ETOX18-01 provides a promising tool for large-scale water environmental assessment, and has a potential application in evaluating the water quality and early risk warning. Highlights: A water-quality early warning instrument is developed for evaluating acute water toxicity. The instrument is based on E. coli integrated electrochemical biosensor. The results of multiple wastewater samples by the instrument show a good correlation with ISO Luminescent bacterial test. The instrument has a more excellent performance for colored water samples than ISO Luminescent bacterial test.